The Recovery of Metal Ions from Spent Catalysts: A Study of Desulfurization Catalysts: Efficient Metal Recovery from Spent Catalysts using Leaching Solutions (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The catalysts used in refining processes are regularly deactivated over time. Typically, the operation of the catalyst can be regenerated and reused, although it is not possible to recycle the catalyst always. Following a few regeneration and reuse cycles, the operation of the catalyst will decrease to very low levels and further regeneration mechanism cannot be achieved economically. In solid waste type, the expended catalysts are disposed of. The disposal of spent catalysts includes respect of rigorous legislation on the climate. Because of the self-heating activity and toxic chemical content, spent hydrotreating catalysts is listed by the Environmental Protection Agency as hazardous waste in the USA. Study on the advancement of processes for the processing and reuse of waste hydrotreating catalysts has resulted in strict environmental controls on the storage of and disposal of spent catalysts. The current study is about recuperation of metals, in particular molybdenum and cobalt from spent catalogs used in desulfurization by leaching using solutions of caustic soda and sulfuric acid. The results have been studied for the purpose of fixing apological solution with the five experimental parameters (leaching solution concentration, solid to liquid ratio, particle size, turbidity and temp). The suggested requirements are 1M for the NaOH solution and 1100 for H2SO4 solution, 1100 ratio of strong catalyst mass in grams to leaching solution volume in milliliters, rhythmic rhythm of agitation of 250 rpm, particulate size less than 150 μm and temperature less than 80°C. The conditions are 47,092 molybdenum extraction and 72, 73 cobalt extraction.